Studying Relationship between (Outer-Inner) Control Source and (Role–Personality) Conflict by Second Level High School Headmasters of Township Khorramabad - Fazallah Mirderikvand (Journal of Global Pharma Technology, 2017)
The aim of this study was to investigate the relationship between control source and role-personality conflict by the second level high school headmasters of township Khorramabad. The Statistical population consisted of all the second level high school headmasters of township Khorramabad in the academic year 2014-15; among them 65 headmasters (35 men and 30 women) were selected as sample. In this research the Rotter's control scale (1966) role-personality conflict questionnaire of Rizzo, House and Lirtzman (1970) were used. The results of the data analysis showed there is a significant and positive relationship between outer control source and role-personality conflict by the second level high school headmasters of township Khorram Abad (0/01). This relationship was also confirmed for male and female headmasters separately (0/01). There was not resulted any significant difference between the average scores of headmasters' control source by male headmasters and the average scores of control source by female headmasters. Also there was not observed any significant difference between the average scores of headmasters' role-personality conflict by male headmasters and the average scores of role-personality conflict by female headmasters.Keywords: Managers, Control source, Role-personality Conflict.